57Fe Mossbauer investigations in GaAs and GaP following implantation of 57Mn* - Masenda, Hilary (My University, 2010)
The incorporation of extrinsic defects in semiconductors by ion implantation and appropriate annealing gives rise to instabilities that profoundly affect their electronic and optical properties. Consequently, the knowledge of site location and hence the chemical nature of these defects is vital for the understanding of new properties in doped compound semiconductors. These properties are important for possible applications in optoelectronic and high-frequency devices such as light emitting diodes (LEDs), laser diodes, and monolithic microwave integrated circuits (MMICs) and high power field effect transistors (FETs) for satellite and terrestrial communication. Mössbauer studies to investigate site location and nature of Fe complexes formed in GaAs and GaP single crystals following 57Mn* implantation at temperatures 77 – 700 K were carried out at the ISOLDE facility, CERN, Switzerland. The set of temperature dependent spectra for each sample was analyzed with a simultaneous fitting routine. Best fits to the data required four components, an asymmetric doublet due to radiation damage attributed to Fe atoms in small amorphous pockets, two single lines, one assigned to Fe on substitutional Ga sites and the other to Fe in interstitial sites, and a low intensity symmetric doublet assigned to impurity-vacancy complexes. The isomer shift and quadrupole splitting values show the trivalent state of iron (57Fe3+), with a 3d5 electronic configuration, on substitutional Ga sites in cubic environments and, near 3d5 and 3d6 electronic configurations in distorted environments and interstitial sites, respectively. The impurity-vacancy complex is tentatively assigned to 3d5 configuration because of its complex nature. The observed variations in the hyperfine parameters of the damage site in GaAs and GaP at temperatures above 400 K can be attributed to the changes in environment in the neighborhood of the Mössbauer atom and possibly in the Fe-defect bonding mechanism. Different annealing stages of the radiation damage in the two substrates were evident, with more pronounced healing observed in GaAs (350 – 550 K) as compared to GaP (465 – 600 K). This is attributed to Fe forming stronger bonds with P than As. This observation is further supported by the higher Debye temperatures that were extracted for the different components in GaP relative to GaAs. In the III-V semiconductors, Fe atoms on substitutional III sites are known to be deep acceptors and to have a tendency to interfere mainly with the optical functionality of the semiconductors. In this regard, recommendations to investigate optical properties and electrical conductivity of these materials are discussed.